When collateral vessels matter: asymptomatic Leriche syndrome. Issue 11 (10th September 2015) - Morotti, Alessandro; Busso, Marco; Cinardo, Paola; Bonomo, Katia; Angelino, Valeria; Cardinale, Luciano; Veltri, Andrea; Guerrasio, Angelo
Key Clinical Message: While acute arterial occlusion causes life‐threatening ischemia and organ damage requiring urgent revascularization, the incidental identification of arterial occlusions in asymptomatic patients represents a therapeutic dilemma in clinicians. Does chronic asymptomatic artery occlusion require specific treatment? Abstract : While acute arterial occlusion causes life‐threatening ischemia and organ damage requiring urgent revascularization, the incidental identification of arterial occlusions in asymptomatic patients represents a therapeutic dilemma in clinicians. Does chronic asymptomatic artery occlusion require specific treatment?